An Aspect of Post Graduate Diploma in Police Science (PGDPS) Program - Adhikari, Hari Prasad (Journal of Business and Social Sciences, 2024)
The aim of faculty of management’s Post Graduate Diploma in Police Sciences (PGDPS) is to develop creative, result oriented and socially responsible police professionals to fill up the middle level positions in Police Organization of Nepal. This course also provide theoretical knowledge, practical skills, research oriented activities and undertaking of general and specialized areas of police service and relevant areas that support the functions of police administration/ operation. The methodology is used for the study of the descriptive one based on survey method. The present article covers the background and issues of PGDPS, Objectives of the study, Scope and Limitation of the Study, Methodology, analysis of opinions of the Products of PGDPS Program, Role of Government and regulative organizations in Program Improvement, Analysis of The views of Faculty Members Regarding the PGDPS Program and suggestions.